Nanomodulation and nanotherapeutics of tumor-microenvironment - Rupal Dubey; Sourbh Suren Garg; Jeena Gupta (Elsevier, 2022)
The kind of environment that is present around the tumor is called the tumor microenvironment (TME). Various factors responsible for developing the TME are hypoxia, acidosis, fibroblasts, and macrophages, upregulation of interstitial fluid pressure (IFP), extracellular matrix (ECM), and angiogenesis. The nanoformulations in conjugation with anticancer drugs improves drug retention time and allows drug release at very low doses. Administration of the drug in small doses allows the drug to show its therapeutic potential effectively and minimizes the risk of its accumulation in other tissues, thereby reducing the risk of toxicity. In this review article, we reviewed the result of published reports and attempted to discuss the mechanisms of different nanoformulations (nanoparticle, nanoemulsion, nanocomposites, and nanobubbles) to ameliorate the TME. Advancements in our knowledge about the TME help scientists design novel nanoformulations for treating cancer.